2007
DOI: 10.3354/meps340089
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale variability in the dispersion of the sea urchin Heliocidaris erythrogramma among boulders

Abstract: Densities of many organisms, particularly invertebrates, are inherently patchy from place to place, with much variability at small spatial scales. Intertidal and shallow subtidal boulder fields in New South Wales, Australia, support a diverse suite of species, many of which have very patchy distributions among boulders. In this study, the purple urchin Heliocidaris erythrogramma was very patchily distributed at small spatial scales, being abundant under some boulders and absent from others. This pattern was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…For example, in the first approach, recruit abundances are correlated with habitat characteristics (e.g., urchin recruits were correlated with characteristics of intertidal boulders; Smoothey and Chapman 2007), while in the second, settlers are provided with a choice of different habitat types in a controlled experiment (Botero and Atema 1982). Commonly, individuals are monitored through time following settlement to relate subsequent performance to habitat selection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the first approach, recruit abundances are correlated with habitat characteristics (e.g., urchin recruits were correlated with characteristics of intertidal boulders; Smoothey and Chapman 2007), while in the second, settlers are provided with a choice of different habitat types in a controlled experiment (Botero and Atema 1982). Commonly, individuals are monitored through time following settlement to relate subsequent performance to habitat selection.…”
Section: Introductionmentioning
confidence: 99%
“…A second conclusion is that some life‐history trait of H. bajulus other than the evolution of large egg size and potentially high risk or cost of polyspermy (which it shares in common with H. erythrogramma and their common ancestor) must account for the significantly lower rate of nonsynonymous bindin nucleotide substitution that evolved secondarily in H. bajulus . That specific life‐history difference is not known, but a plausible candidate difference is the very high spatial density of adult H. erythrogramma (Wright et al 2005; Smoothey and Chapman 2007) relative to both H. bajulus and H . tuberculata (Cole et al 1992), leading to sperm competition and sexual conflict (Denny and Shibata 1989; Levitan and Young 1995; Lauzon‐Guay and Scheibling 2007), and relatively high rates of nonsynonymous bindin substitutions at a few sites in H .…”
Section: Discussionmentioning
confidence: 99%
“…Heliocidaris bajulus (Dartnall 1972) is endemic to the eastern shores of Tasmania, where its total known geographic range is <500 km (Dartnall 1972; Rowe and Gates 1995). There are no quantitative analyses of H. bajulus distribution and abundance, but qualitative surveys by one of us (R. Emlet) at several intertidal sites suggest that adults live under rocks at relatively low densities (<1 m −2 ) similar to H. tuberculata (Cole et al 1992), but much lower than adult H. erythrogramma densities (about 10 m −2 , up to 100 m −2 in dense feeding aggregations; Wright et al 2005; Smoothey and Chapman 2007). Males are broadcast spawners with typical‐sized testes like other Heliocidaris species.…”
Section: Methodsmentioning
confidence: 99%
“…Smoothey and Chapman (2007) showed that, like these Ischnochiton species, this urchin is aggregated on certain boulders and there appears to be some effect of conspecifics contributing to this pattern. The urchin Heliocidaris erythrogramma also inhabits boulder fields in NSW.…”
Section: Genetics Of Groups Of Ischnochiton Under Bouldersmentioning
confidence: 94%